Analysis of Merdeka Curriculum-based Electronic Module Needs for Physics Learning Phase F - Prastyo, Agung; Ekawati, Elvin Yusliana; Zahroh, Shofi Hikmatuz (FKIP - Universitas Riau, 2024)
This study aims to define the need for Merdeka curriculum-based electronic modules for physics learning phase F. This research uses a qualitative approach with a descriptive research type. Data was collected through interviews, questionnaires, and observation. The results showed that teachers and students used technology in learning physics. They realize that using teaching materials such as electronic modules based on the Merdeka curriculum is essential. However, the number of physics teaching materials is still limited, especially the electronic modules for physics learning phase F. Phase F teachers and students need physics teaching materials based on a Merdeka curriculum. Some students who have not met the minimum learning outcomes try to find these teaching materials through tutoring outside of school. Indicators of Merdeka curriculum-based teaching materials include: 1) teaching materials have process skill syntax, 2) learning is structured using the Understanding by Design approach, and 3) teaching materials have components that support strengthening the Profil Pelajar Pancasila in learning. This is by the mandate of learning in the Merdeka curriculum. The development of physics teaching materials needs to be done to achieve the objectives of learning physics in the Merdeka curriculum.